An intergroup approach to collective narcissism: Intergroup threats and hostility in four European Union countries. (February 2022) - Guerra, Rita; Bierwiaczonek, Kinga; Ferreira, Marina; Golec de Zavala, Agnieszka; Abakoumkin, Georgios; Wildschut, Tim; Sedikides, Constantine
Although it is known that collective narcissism is associated with problematic intergroup relations, its predictors are less well understood. Two studies, conducted in four European Union countries (Germany, Greece, Portugal, the United Kingdom [UK]), tested the hypotheses that integrated (i.e., realistic and symbolic) threat (Study 1, N = 936) as well as distinctiveness threat (Study 2, N = 434) positively predict national collective narcissism and national ingroup satisfaction, but that only national collective narcissism predicts problematic intergroup relations in reference to threatening outgroups. The results were consistent with those hypotheses. The two types of threat predicted increased national collective narcissism and national ingroup satisfaction. However, only national collective narcissism was associated with negative emotions and hostile behavioral intentions toward the threatening outgroups, when its overlap with national ingroup satisfaction was partialled out. These cross-national findings advanced knowledge of predictors, as well as consequences, of collective narcissism.